Pengaruh Customer Experience Terhadap Brand Switching dengan Mediasi Electronic Word of Mouth pada Pengguna TikTok Shop Indonesia - Muhammad Exsel Al Syiamudawan; Rohimat Nurhasan; Fikri Fahru Roji (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
The purpose of this research is to identify the influence between customer experience and brand switching via the mediating role of electronic word of mouth. Users of TikTok Shop in Indonesia were the subjects of the research. Customer Experience (X) is an exogenous variable, Brand Switching (Y) is an endogenous variable, and Electronic Word of Mouth (Z) is an intervening variable in this quantitative research. The researchers in this study used a non-probability strategy based on purposive sampling and sent questionnaires to respondent. A technique called Partial Least Squares Structural Equation Modeling (PLS-SEM) was used to assess the association between variables when the acquired data was processed. Positive and statistically significant effects of Customer Experience on E-WOM and Brand Switching were observed. Furthermore, it was shown that E-WOM significantly and positively impacts brand switching. In the link between Customer Experience and Brand Switching, E-WOM was shown to have a major moderating role. This demonstrates that consumer choices to select e-commerce is influenced by the strength of the pleasant customer experience, which in turn increases the motivation for effective communication and engagement among users on digital platforms.